Learn salesforce lightning : the visual guide to the lightning UI - Duarte, Felicia; Hoffman, Rachelle (Apress, 2018)
"Refer to this invaluable how-to guide for basic training on Salesforce Lightning. Salespeople and technical users and consultants will no longer have to resort to learning the interface on their own, which is very time consuming. Learn Salesforce Lightning is a step-by-step visual guide that offers immediate and valuable solutions to the new set of UI tools included in Lightning. With chapters broken down into easily absorbed topics, you walk through the entire process of managing your daily activities within Salesforce, as well as basic customizations and system management. The book explains the primary use cases for Lighting, and simplifies some of the more complex features, such as opportunity stage management and the new dashboard builder. Topics covered include: Sales and service managementLightning Apps on the AppExchangeLightning dashboards and reportsLightning securityLightning Process Builder and more What You'll Learn Navigate the Salesforce Lightning interfaceKnow where to go in the setup area to make customizationsCreate dynamic reports and dashboardsView Lightning on a mobile deviceTrain other users on common day-to-day activities within Lightning Who This Book Is for Salespeople, managers, and executives who are currently evaluating Salesforce.com, who recently purchased a license with Salesforce.com, or recently upgraded to the Lightning user interface. This book is also for Salesforce administrators, consultants, project managers, and technical users looking for basic training on Salesforce Lightning."--Provided by publisher